The determination of normal stresses in cross-sections of the three-flue reinforced concrete chimney - Małgorzata Dobrowolska; Marta Słowik (Budownictwo i Architektura, 2008)
In the paper there is presented the algorithm of calculation of normal stresses in reinforced concrete three-flue chimney. The calculation has been made for full cross-section and for cross-section weakened by openings. The governing equations has been derived in an analytical form assuming linear physical laws for concrete and steel and, as for as considered cross-section weakened by openings, taking into account the additional reinforcing steel bars at the openings. In addition coefficients B and C have been determined, which are useful at dimensioning.